1994
DOI: 10.1007/bf02033717
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies differences and variability with time of protein precipitation activity of extractable tannins, crude protein, ash, and dry matter content of leaves from 13 species of Nepalese fodder trees

Abstract: Dry matter, ash, crude protein, and protein precipitation activity (PPA) of 13 Nepalese tree fodder species were monitored in dried samples prepared monthly between November 1990 and May 1991, and additionally in November 1991, covering the season when they are particularly important as fodder. Monthly levels of dry matter, ash, and crude protein were fairly stable except when there was new leaf growth, although year to year differences in dry matter were found inBrassaiopsis hainla (Bh),Dendrocalamus strictus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The DM content was higher for BP (P < 0.05) than AL and FR, but there was no difference (P > 0.05) between the other species of tree fodders. The values were comparable to the earlier reports for the same species of tree fodder harvested at similar times of the year (Khanal and Subba 2001, Throne et al 1999, Wood et al 1994. The DM content would increase with the increasing maturity, which was probably another reason why it is higher for BP that was approaching fruit bearing stage.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The DM content was higher for BP (P < 0.05) than AL and FR, but there was no difference (P > 0.05) between the other species of tree fodders. The values were comparable to the earlier reports for the same species of tree fodder harvested at similar times of the year (Khanal and Subba 2001, Throne et al 1999, Wood et al 1994. The DM content would increase with the increasing maturity, which was probably another reason why it is higher for BP that was approaching fruit bearing stage.…”
Section: Resultssupporting
confidence: 89%
“…While leaves and twigs were included in the current study to represent the actual feeding practices of the farmers, it was only the leaves that were used to determine CP content previously (Khanal and Subba 2001). Time of harvest also affect the CP content with the same species of tree fodder varying in CP content by about 30 to 40% when harvested at different times of the year (Topps 1992, Wood et al 1994. Nonetheless, all of them could be regarded to have medium CP content, which could make a valuable source of protein for ruminants.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the investigation of CT composition and content using their reaction with butanol/HCl, protein precipitation activity was estimated by the radial diffusion method of Hagerman,23 modified by substituting bovine haemoglobin (Sigma‐Aldrich, Poole, UK) for bovine serum albumin to make the rings more clearly visible 24. Petri dishes were prepared with agarose gel (1% w/v) containing 0.1% haemoglobin.…”
Section: Methodsmentioning
confidence: 99%
“…A study in the middle hills (900-2,000 m altitude) in eastern Nepal identified 14 major fodder tree species used principally in the winter and dry seasons (November-June) to supplement crop residues in ruminant feeds. In this region, tanniniferous tree fodder contributed over 15 % of the dry matter and over 20 % of the crude protein to the diet, but actual usage on individual farms varied depending on the ethnic and social group of the farmers, possible as a result of different livestock holdings and opportunities for planting trees [76,205,212,223].…”
Section: Importance Of Tanniniferous Feeds and Foragesmentioning
confidence: 99%